2016
DOI: 10.1186/s40064-016-2224-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific regulation of potassium homeostasis by high doses of cationic amino acids

Abstract: The administration of l-arginine hydrochloride has been used for testing pituitary secretion in humans, and as an experimental model for induction of acute pancreatitis in rats and mice. Whereas in the first case, the administration of the amino acid is associated with hiperkalemia, in the model of acute pancreatitis no data are available on possible changes in potassium homeostasis. The present study shows that the acute administration to mice of l-arginine hydrochloride or other cationic amino acids almost d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…Disturbance in serum potassium levels, either an increase or decrease, is almost certainly the consequence of kidney disorder or related to a certain degree to kidney dysfunction. Different studies described that the efflux of potassium from cells to the extracellular spaces was associated with administering L-arginine and other cationic amino acids [24]. The results from the present study emphasized the significant effect of thymol and carvacrol applied in combination on a decrease in the potassium serum level (Table 1), contributing to the fine regulation of cation homeostasis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Disturbance in serum potassium levels, either an increase or decrease, is almost certainly the consequence of kidney disorder or related to a certain degree to kidney dysfunction. Different studies described that the efflux of potassium from cells to the extracellular spaces was associated with administering L-arginine and other cationic amino acids [24]. The results from the present study emphasized the significant effect of thymol and carvacrol applied in combination on a decrease in the potassium serum level (Table 1), contributing to the fine regulation of cation homeostasis.…”
Section: Discussionsupporting
confidence: 69%
“…A recently published study also revealed that the systemic (i.p.) application of L-arginine produced a marked rise in plasma potassium levels in mice [24]. Potassium is required for vital cellular function, and even small changes in the distribution between intra-and extracellular compartments can result in a marked elevation in serum potassium values [25].…”
Section: Discussionmentioning
confidence: 99%
“…Similar chemical shis were also observed for L-arginine hydrochloride or L-histidine hydrochloride, which has been reported in the literature to indicate the cationic form. 31,32 The abovementioned shis are shown in Fig. 2 and S17 (ESI †) for 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…L-arginine also induced hyperkalaemia in animals and humans [73]. A recent study suggested that L-arginine and other dibasic amino acids increased plasma potassium levels, promoting the metal ion efflux from liver and pancreas to the extracellular aqueous environment [74].…”
Section: Side Effects Mechanism Of Toxicity and Interactionsmentioning
confidence: 98%